2018
DOI: 10.1016/j.jdermsci.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The retinoid X receptor agonist, 9-cis UAB30, inhibits cutaneous T-cell lymphoma proliferation through the SKP2-p27kip1 axis

Abstract: UAB30 and bexarotene induce both early cell apoptosis and suppress cell proliferation. Inhibition of the G1 to S cell cycle transition by rexinoids is mediated, in part, through downregulation of SKP2 and/or 20S proteasome activity, leading to increased p27kip1 protein stability. Because UAB30 has minimal effect in elevating serum TGs and inducing hypothyroidism, it is potentially a better alternative to bexarotene for the treatment of CTCLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Bexarotene is a third-generation retinoid X receptor (RXR)-selective retinoid that has been approved for use in the treatment of both early and advanced CTCL (79). Although bexarotene has been used for decades in the treatment of CTCL, and several preclinical studies have suggested anti-CTCL mechanisms are involved in the efficacy of this drug (1012), little is known about the exact mechanisms underlying its anti-tumor effects in CTCL patients in vivo (79, 11, 12). Since bexarotene is useful for both early and advanced CTCL, bexarotene is applied in the real world to ultraviolet-tolerant early CTCL patients as a first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Bexarotene is a third-generation retinoid X receptor (RXR)-selective retinoid that has been approved for use in the treatment of both early and advanced CTCL (79). Although bexarotene has been used for decades in the treatment of CTCL, and several preclinical studies have suggested anti-CTCL mechanisms are involved in the efficacy of this drug (1012), little is known about the exact mechanisms underlying its anti-tumor effects in CTCL patients in vivo (79, 11, 12). Since bexarotene is useful for both early and advanced CTCL, bexarotene is applied in the real world to ultraviolet-tolerant early CTCL patients as a first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Retinoids, and particularly RA, have been shown to affect cell-cycle progression in a variety of cancer cell lines [ [40] , [41] , [42] , [43] ] including neuroblastoma [ [44] , [45] , [46] ]. UAB30 has also been shown to induce G0/G1 cell-cycle arrest in rhabdomyosarcoma [ 47 ], hepatoblastoma [ 48 ], and neuroblastoma [ 13 , 14 ] cell lines. In this study, we showed that treatment of COA3 with RA and both PDXs with UAB30 caused a dose-dependent block in the G1/S transition triggering a decreased S phase and an increased percentage of cells in the G1 phase, a critical stage for cell differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…RA has numerous undesirable side effects, including hepatotoxicity, mucocutaneous disorders, and hypertriglyceridemia, that may limit the dosing amount and duration of treatment [ 10 , 11 ]. 9- cis -UAB30 (8-(3′,4′-dihydro-1′(2′H)-naphthalen-1′-ylidene)-3,7-dimethyl-2,4,6-octatrienoic acid, UAB30) is a novel retinoid X receptor (RXR) agonist that has demonstrated similar efficacy but a minimal toxicity profile when compared to RA [ 12 , 13 ]. Our laboratory has previously shown the effectiveness of UAB30 in long-term passage neuroblastoma cell lines in decreasing proliferation, viability, and motility in vitro , as well as tumor growth in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bexarotene is the only U.S. Food and Drug Administration (FDA) approved agonist for RXR, and it is used clinically for the treatment of cutaneous T-cell lymphomas (CTCLs). 32 Bexarotene has been shown to be an effective chemopreventive agent preclinically and clinically, including those for lung cancer. 11,12,33 In our previous study, we found that aerosolized bexarotene with DMSO/ethanol as solvent significantly decreased lung tumorigenesis in a B(a)P-induced mouse lung adenoma model.…”
Section: Nano Lettersmentioning
confidence: 99%